The Six Sigma Approach for the Development of Accounting Information System Performance - Hendra Gunawan; Himmatun Karimah (Journal of Applied Accounting and Taxation, 2017)
The study investigates six sigma approach in manufacturing companies to prove its influence on the development of accounting information systems performance. Total of 80 respondent data from processed questionnaire consist of low management (64%), middle management (38%) and top management (7%). Statistically significant were found for application six sigma and development of accounting information systems performance. The result shows six sigma has significant effect to accounting information system performance. The findings show that companies implement six sigma at high altitudes. Six sigma has criteria such as support and commitment from top management, organizational culture, customer focus, and training. Criteria for support and commitment from top management and organizational culture are not proven to significantly influence the development of accounting information system performance.